Atención al cliente en la Cooperativa de Ahorro y Crédito “Juan Pio De Mora”. - Villegas Chimborazo, Arianna Mayling (2022)
This study focuses on the customer service of the "JUAN PIO DE MORA" Savings and Credit Cooperative. Its objective is to investigate the type of attention that clients receive through direct observation and the application of surveys to establish factors that help improve the attention to clients of this institution. The Juan Pio de Mora cooperative is specifically oriented to the financial part, such as savings and credit services for its members, but it also prioritized the humanistic, social and supportive part. This cooperative is supervised by the Superintendence of Popular and Solidarity Economy, and by the Deposit Insurance Corporation, which offers security to all its clients. The problem identified in the Juan Pio de Mora Savings and Credit Cooperative is that the customer service system is dissatisfied by customers: it takes time to provide information or meet their requirements, often lack of preparation and little Professionalism on the part of the personnel that works in the company makes it difficult for the activities to be carried out immediately, which intends to establish strategies and models to improve the quality of customer service.